Animasi dengan Efek Ilustrasi Pensil (2d) pada Video Klip Musik - Satrya Mahardhika; Ardiyan Ardiyan; Ardiyansah Ardiyansah (Humaniora, 2010)
This research is to explore various styles of animation in making video clip of a new band. Besides defining the exact visual style, the process is important to bring animation out of 2D-3D dichotomy. Doodle style is chosen as it suits particular theme of the band’s songs and music genre. Meanwhile, the style defining is related to the efficiency and efforts to be out of mindset that animation is just about technique skill instead of about creativity.